2023
DOI: 10.3389/fgene.2023.1225158
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-related genes involved in renal carcinoma progression

Jose María Zamora-Fuentes,
Enrique Hernández-Lemus,
Jesús Espinal-Enríquez

Abstract: Renal carcinomas are a group of malignant tumors often originating in the cells lining the small tubes in the kidney responsible for filtering waste from the blood and urine production. Kidney tumors arise from the uncontrolled growth of cells in the kidneys and are responsible for a large share of global cancer-related morbidity and mortality. Understanding the molecular mechanisms driving renal carcinoma progression results crucial for the development of targeted therapies leading to an improvement of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Finally, we also investigated whether the methylation profile of DNA may be involved in this loss of long-range co-expression in cancer. We showed that, despite the fact that methylation profile does exert influence on particular genes that may affect the cell states depending on the progression stage [28], we cannot establish a clear association between methylation profiles and co-expression between neighboring genes.…”
Section: Loss Of Long-range Co-expression In Cancermentioning
confidence: 64%
“…Finally, we also investigated whether the methylation profile of DNA may be involved in this loss of long-range co-expression in cancer. We showed that, despite the fact that methylation profile does exert influence on particular genes that may affect the cell states depending on the progression stage [28], we cannot establish a clear association between methylation profiles and co-expression between neighboring genes.…”
Section: Loss Of Long-range Co-expression In Cancermentioning
confidence: 64%
“…The genes in cancerous samples tend to co-express mainly with their nearest neighbors and lose co-expression relations with medium and long distance genes. This phenomenon has been observed in lung cancer (Andonegui-Elguera et al, 2021), clear cell renal carcinoma (Zamora-Fuentes et al, 2020;Zamora-Fuentes et al, 2022), as well as other thirteen types of cancer (Garcia-Cortes et al, 2022).…”
Section: Introductionmentioning
confidence: 68%